Corak Ideologis Partai Politik Islam - Ihsan, A. Bakir (Jurnal Review Politik, 2017)
One of the agenda of political parties (based on) Islam in Indonesia is the coloring legislation with Islamic values, including legislation for public interest. Islam as a religion with its distinctive teaching device can be a problem dealing with pluralistic social reality, both religion and cultural. Therefore, standard formulation is required in formulating Islamic values to be part of the legislation so that it can be accepted by the public in general. This is where Islamic political parties are required to have the ability to formulate Islamic values as the implementation as well as the type of Islam as the principle of political parties.